Swedish Child Health Services Register: a quality register for child health services and children's well-being - Thomas Wallby; Anna Erica Fäldt; Karin Berg; Mattias Wennergren; Ann-Sofie Frisk Cavefors; Helena Edin; Leif Ekholm; Lars Gelander; Marie Golsäter; Jennie Hedman; Anton Holmgren; Frida Karlsson Videhult; et al. (BMJ Publishing Group, 2023)
Background Swedish child health services (CHS) is a free-of-charge healthcare system that reaches almost all children under the age of 6. The aim for the CHS is to improve children's physical, psychological and social health by promoting health and development, preventing illness and detecting emerging problems early in the child's life. The services are defined in a national programme divided into three parts: universal interventions, targeted interventions and indicated interventions.The Swedish Child Health Services Register (BHVQ) is a national Quality Register developed in 2013. The register extracts data from the child's health record and automatically presents current data in real time. At present, the register includes 21 variables.Aim We aim to describe data available in the BHVQ and the completeness of data in BHVQ across variables.Methods Child-specific data were exported from the register, and data for children born in the regions were retrieved from Statistics Sweden to calculate coverage.Results The register includes over 110 000 children born between 2011 and 2022 from 221 child healthcare centres in eight of Sweden's 21 regions. In seven of the eight regions, 100% of centres report data.The completeness of data differs between participating regions and birth cohorts. The average coverage for children born in 2021 is 71%.Conclusions The BHVQ is a valuable resource for evaluating Child Health Services nationally, with high coverage for the youngest children. As a result of continuous improvement of the services, the possibility to follow the development of children's health in Sweden is possible through the register. When fully expanded, the register will be a natural and essential part of developing preventive services, improving healthcare for children below 6 years of age and a tool for developing evidence-based child health interventions.